Islam in Process Historical and Civilizational Perspectives (Yearbook of the Sociology of Islam 7) - Arnason, Johann P.; Salvatore, Armando; Stauth, Georg (Globaler lokaler Islam, 2007)
The articles included in this Yearbook of the Sociology of Islam are focused on two perspectives: Some link the comparative analysis of Islam to ongoing debates on the Axial Age and its role in the formation of major civilizational complexes, while others are more concerned with the historical constellations and sources involved in the formation of Islam as a religion and a civilization. More than any other particular line of inquiry, new historical and sociological approaches to the Axial Age revived the idea of comparative civilizational analysis and channeled it into more specific projects. A closer look at the very problematic place of Islam in this context will help to clarify questions about the Axial version of civilizational theory as well as issues in Islamic studies and sociological approaches to modern Islam. Contributors among others: Said Arjomand, Shmuel N. Eisenstadt, Josef van Ess and Raif G. Khoury.